Catalytic performance of nickel(II) complexes bearing 1, 10-phenanthroline based ligands in homogeneous ethylene oligomerization. (1st September 2022) - Bekmukhamedov, Giyjaz E.; Sukhov, Aleksandr V.; Kuchkaev, Aidar M.; Kuchkaev, Airat M.; Khayarov, Khasan R.; Dobrynin, Alexey B.; Babaev, Vasily M.; Yakhvarov, Dmitry G.
Graphical abstract: A comparative analysis of the activity of 1, 10-phenanthroline nickel(II) complexes in ethylene oligomerization has been performed. The insertion of the 5, 6-carbonyl groups to 1, 10-phenanthroline leads to an increase in activity. Methyl groups at the 2- and 9-positions of 1, 10-phenanthroline cause a decrease in activity and an increase in selectivity for butenes. The replacement of bromide by mesityl with the formation of a Ni–C bond leads to an increase in activity. Abstract: A comparative study of catalytic activity of nickel(II) complexes bearing 1, 10-phenanthroline ( phen ) based ligands in homogeneous ethylene oligomerization process has been performed. It was found that activated by methylaluminoxane (MMAO-12), [NiBr2 ( phen )] complex oligomerizes ethylene with the moderate activity (66.2 × 10 3 molC2H4 ∙molNi −1 ∙h −1 ) to the wide range (C4 –C20 ) of even-numbered olefins, with a selectivity for linear alpha-olefins of 43%. The insertion of the carbonyl groups at the 5- and 6-position of 1, 10-phenanthroline leads to an increase in catalytic activity up to 81.4 × 10 3 molC2H4 ∙molNi −1 ∙h −1 . The presence of hydroxyl groups at the same positions causes a decrease in activity to 15.5 × 10 3 molC 2 H 4 ∙molNi − 1 ∙h −1 . The steric hindrances near the metal center caused by the methyl groups at 2- and 9-position of 2, 9-dimethyl-1, 10-phenanthroline result in a decrease in the activity to (26.8–52.2) × 10 3 molC 2 H 4 ∙molNi −1 ∙h −1 and increasing of the selectivity to butenes to 80–96%. The use of activated by MMAO-12 organonickel sigma-complex [NiBr( Mes )( phen )] (where Mes = 2, 4, 6-trimethylphenyl) bearing Ni–C bond increases the oligomerization activity – the activated complex dimerizes ethylene to mainly butenes with activity of 83.5 × 10 3 molC 2 H 4 ∙molNi −1 ∙h −1 . At the same time, this sigma-complex in combination with Et3 Al2 Cl3 and EtAlCl2 served as activators exhibits higher oligomerization activity – (348.1–394.5) × 10 3 molC 2 H 4 ∙molNi −1 ∙h −1, and lower selectivity to butenes – 58–61%.